ONE STOP INTEGRATED SERVICE MANAGEMENT (PTSP) IN IMPROVING SERVICE QUALITY - Megananda, Nuril Azizah; Karamy, Syakira Selma (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze and understand One Gate Integrated Service Management (PTSP) in improving service quality at MIS At Taqwa Bondowoso . This research was conducted at the Private Islamic Elementary School of At Taqwa Bondowoso , which in this research is called MIS At Taqwa Bondowoso . This study uses a descriptive qualitative research approach using observation, interviews, and documentation method. Data analysis refers to the concept of Miles and Huberman : data collection, data reduction, data presentation, and conclusion. The results of the study show that One Gate Integrated Service Management (PTSP) in improving service quality at MIS At Taqwa Bondowoso includes planning process in the form of procurement of PTSP lobby space, analysis and organization of personnel, analysis and fulfillment of supporting resources; the implementation process of One Gate Integrated Services (PTSP) is divided into seven services: staffing and correspondence services, student services, curriculum services, madrasah operator services, financial services which are divided into BOS treasurer and madrasah treasurer, as well as general administration services ; the evaluation process is carried out every three months in the form of an evaluation meeting led by the Head of the Madrasah.